2020
DOI: 10.1002/advs.202001650
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Structure Engineering of Bioinspired Anisotropic Surface for Droplet Recognition and Transportation

Abstract: Surfaces with tunable liquid adhesion have aroused great attention in past years. However, it remains challenging to endow a surface with the capability of droplet recognition and transportation. Here, a bioinspired surface, termed as TMAS, is presented that is inspired by isotropic lotus leaves and anisotropic butterfly wings. The surface is prepared by simply growing a triangular micropillar array on the pre‐stretched thin poly(dimethylsiloxane) (PDMS) film. The regulation of mechanical stress in the PDMS fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
0
45
0
1
Order By: Relevance
“…The influence of these surface modification procedures on the surface microtopography of silicone films has been extensively investigated 22 , and the formation of sinusoidal surface microtopographies (wrinkles) caused by the mechanical mismatch between stiff surface layers and the soft underlying polymer has been thoroughly examined 22 27 . Mechanically reversible surface topographies have been used to modulate surface wettability 25 , 28 , 29 and adhesion 30 , 31 and in the fabrication of materials for stretchable electronics 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of these surface modification procedures on the surface microtopography of silicone films has been extensively investigated 22 , and the formation of sinusoidal surface microtopographies (wrinkles) caused by the mechanical mismatch between stiff surface layers and the soft underlying polymer has been thoroughly examined 22 27 . Mechanically reversible surface topographies have been used to modulate surface wettability 25 , 28 , 29 and adhesion 30 , 31 and in the fabrication of materials for stretchable electronics 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing the concepts from lotus leaf and butterfly wing, we created a surface that could be used for acid/base recognition by the regulation of mechanical stress and robust transportation of water droplets. [ 4 ] Yu et al. [ 5 ] designed a discontinuous fibrous Bouligand architecture, a combination of Bouligand found in mantis shrimps and nacreous staggered structures found in abalone, showing significantly enhanced fracture resistance and crack orientation insensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Borrowing the concepts from lotus leaf and butterfly wing, we created a surface that could be used for acid/base recognition by the regulation of mechanical stress and robust transportation of water droplets. [4] Yu et al [5] It has long been demonstrated the gecko-inspired micropillar array with T-shape tips possesses the best adhesion performance of a given material. The further enhancement of the adhesion performances of T-shape micropillars can offer redundant adhesion to compensate for the inevitable improper contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Droplet wettability is guided and controlled by artificial microtextured surfaces in many technological applications such as self‐cleaning, [ 1,2 ] droplet recognition, [ 3 ] water harvesting, [ 4,5 ] anti‐ice, [ 6–8 ] condensation heat transfer, [ 9 ] oil–water separation, [ 10 ] microfluidic devices, [ 11–14 ] inkjet printing, [ 15,16 ] and bio‐microarrays for DNA and protein chips. [ 17,18 ] Generally speaking, the dynamic wetting evolution of a droplet on microtextured surfaces depends on not only the macroscopic spreading process and topological changes of droplet shapes, but also the mesoscopic changes of the solid/liquid/vapor triphase interfaces and wetting transition in an isolated cavity.…”
Section: Introductionmentioning
confidence: 99%